Clinical and demographic characteristics of patients with kidney disease presenting at a tertiary hospital for expert care in south-west Nigeria - Dada, Samuel; Rafiu, Mojeed; Akanbi, Olusola; Dada, Oluwamayowa (Journal of Surgery and Medicine, 2019)
Aim: Although chronic kidney disease (CKD) remains an important health challenge in our environment, late presentation of the patient for nephrology care is common. We opined that dissemination of information on the sociodemographic distribution, clinical presentation and common etiology of CKD among our patient will increase individual and medical professionals’ awareness of the disease. In addition, it is believed that this will ultimately result in lower threshold for screening and early referral for specialist renal care. Methods: This was a cross-sectional descriptive study involving 152 patients with any form of renal disease either seen primarily at, or referred to the adult nephrology clinic of the hospitals between January 2013 and December 2015. The socio-demographic parameters, clinical characteristic and laboratory data were extracted with a proforma designed for data collection. Results: Of the 152 patients analyzed, 87 (57.24%) were males. The mean age was 49.29±15.92 years. About one quarter were within the age range 51-60 years. More than half (53.9%) were rural dweller. Common indication for referral includes abnormal renal ultrasound findings, elevated serum creatinine and urea, and abnormalities in urine analysis. Malaise, reduce urinary flow and body swelling were the common symptoms at presentation in 50.65%, 40.1% and 34.2% respectively among the patients. The median eGFR was 18.78 (7.86-84.55) ml/min/1.73m2. Across all age groups, majority (48.0%) presented in stage 5 CKD. Hypertensive nephrosclerosis (27.0%), chronic glomerulonephritis (14.5%) and diabetes nephropathy (9.2%) were found to be the leading causes of CKD. Majority of the patients (40.8%) were worked up for and commenced on hemodialysis soon after presentation. Among the end stage renal disease patient, only 7 (4.6%) had renal transplantation at referred centers. Focal segmental glomerulosclerosis was the commonest histological findings among the nephrotic syndrome patient while membranous nephropathy was documented in only 2 patients. Conclusion: Most patients present to the nephrology clinic of our hospital at advanced stage of CKD. We observed that hypertensive nephrosclerosis and glomerulonephritis are the leading causes of their kidney disease.